"Go Hard, Go Early": Preliminary Lessons From New Zealand's Response to COVID-19. Issue 6 (August 2020) - Jamieson, Thomas
Although the full impact of the novel coronavirus (COVID-19) pandemic is yet to be realized, New Zealand has suffered comparatively less than other countries, and there were no active cases in the country by June 8, 2020. Building from best practices in emergency management research, several preliminary lessons emerge from the country's response to the crisis that could be adapted for other settings. In particular, the government acted early and decisively, developed national unity to combat the virus, communicated effectively with the public, and adapted to changing circumstances, especially to address shortcomings in the response. These preliminary lessons provide some guidance in how to effectively respond to the virus through proactive, evidence-based, well-communicated policies.